ORGANIZATIONAL BEHAVIOR DETERMINATION AND DECISION MAKING: ANALYSIS OF SKILLS, MOTIVATION AND COMMUNICATION (LITERATURE REVIEW OF HUMAN RESOURCE MANAGEMENT) - Putra, Rio; Hapzi Ali (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and influence of relationships or influences between variables. This reviewed Organizational Behavior Determination and Decision Making: Analysis of Skills, Motivation and Communication, A Literature Study of Human Resource Management. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The result of this research library is that: 1) The Influence of Organizational Behavior on Organizational Behavior; 2) The Influence of Motivation on Organizational Behavior; 3) The Influence of Communication on Organizational Behavior; 4) Influence of Organizational Behavior on Decision Making; 5) Influence of Motivation on Decision Making; 6) The Influence of Communication on Decision Making; and 7) Influence of Organizational Behavior on Decision Making.